A Rare Case of Craniopharyngioma in the Temporal Lobe - Sasan Razmjoo; Seyed Nematollah Jazayeri; Mohammad Bahadoram; Maedeh Barahman (Case Reports in Neurological Medicine)
Herein, we report on a rare case of craniopharyngioma arising in the left temporal lobe with no prior history of head trauma or surgery. There was a solid-cystic mass in the left temporal lobe on MR images. To the best of our knowledge, this is the second case of a craniopharyngioma occurring in the temporal lobe.